Semiotikk som indre eksil: Om binære modellars rolle i russisk kultur - Mjør, Kåre Johan (Nordlit, 2005)
The article consists of a critical discussion Jurij Lotman and Boris Uspenskij's (in)famous theory of Russian culture possessing an underlying dual (binary) structure and of a contextualisation of their ideas in relation to both their contemporary Soviet situation and possible historical predecessors.